2015
DOI: 10.1037/a0038634
|View full text |Cite
|
Sign up to set email alerts
|

Work demands, family demands, and BMI in dual-earners families: A 16-year longitudinal study.

Abstract: Many scholars assert that work and family demands are negatively related to individuals' long-term physical health, but few studies have explicitly examined this relationship. Among these exceptions, most have employed a cross-sectional design that is limited in its ability to establish causality. We use body mass index (BMI) that generally increases during one's lifetime as an indicator of physical health, and seek to explore the amount of control individuals may have on this seemingly inevitable progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
(79 reference statements)
2
20
0
1
Order By: Relevance
“…Although we could not directly test the mediating processes proposed by the AL model, this finding provides evidence that the job demands-control interaction operates in a similar fashion on BMI, a "secondary" strain outcome in the AL model, as it does on death. This finding contributes to recent research in the applied psychology field showing that work and family demands lead to increases in the growth rate of BMI over time (Kramer & Chung, 2015) by examining how job control can help lessen (or augment) BMI increases over time.…”
Section: Theoretical Implicationssupporting
confidence: 58%
See 2 more Smart Citations
“…Although we could not directly test the mediating processes proposed by the AL model, this finding provides evidence that the job demands-control interaction operates in a similar fashion on BMI, a "secondary" strain outcome in the AL model, as it does on death. This finding contributes to recent research in the applied psychology field showing that work and family demands lead to increases in the growth rate of BMI over time (Kramer & Chung, 2015) by examining how job control can help lessen (or augment) BMI increases over time.…”
Section: Theoretical Implicationssupporting
confidence: 58%
“…The simple slope of the low job control line was statistically significant ( b = .82, p < .05) whereas the slope of the high control line was not ( b = –.18, ns ). Although the magnitude of these results was small, it is important to note that it is not atypical to find small effects of job demands on BMI (Kramer & Chung, ), and that even small changes in BMI can lead to a large increase in risk of death (Berrington de Gonzalez et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Friedman and Greenhaus () recognize the importance of financial resources from both work (e.g., income) and family (e.g., partner financial support) domains, and in particular, the removal of financial resources, as prominent influences on WFC. Whereas researchers have established the relation of WFC to greater stress and poorer health (e.g., Grandey & Cropanzano, ; Kramer & Chung, ), applied psychologists have not often assessed the relationship between financial insecurity and work–family experiences. This is surprising given that, according to the American Psychological Association, money is reported by individuals as the greatest source of stress (http://www.apa.org/monitor/2011/01/stressed-america.aspx).…”
Section: Introductionmentioning
confidence: 99%
“…In their time‐lagged study, Grandey and Cropanzano () used path analysis to show that WFC predicted poor physical health across time (Grandey & Cropanzano, ). COR has also been used to theorize that when resources are allocated to meeting work and family demands, they are unavailable for health‐promoting behaviours such as healthy eating, sleeping, and exercising (Kramer & Chung, ). In fact, Kramer and Chung found that work and family demands have small, but significant negative effects on long‐term physical health (i.e., body mass index).…”
Section: Introductionmentioning
confidence: 99%